1994
DOI: 10.1523/jneurosci.14-08-04965.1994
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory actions of delta 1-, delta 2-, and mu-opioid receptor agonists on excitatory transmission in lamina II neurons of adult rat spinal cord

Abstract: This study examined the electrophysiological consequences of selective activation of delta 1-, delta 2-, or mu-opioid receptors using whole-cell recordings made from visually identified lamina II neurons in thin transverse slices of young adult rat lumbar spinal cord. Excitatory postsynaptic currents (EPSCs) or potentials (EPSPs) were evoked electrically at the ipsilateral dorsal root entry zone after blocking inhibitory inputs with bicuculline and strychnine, and NMDA receptors with D-2-amino-5-phosphonopenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
71
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 38 publications
16
71
0
Order By: Relevance
“…Indeed, considerable evidence argues that MORand DOR-selective agents inhibit excitatory (glutamatergic) neurotransmitter release by C-fibers in a more potent manner than how they inhibit intrinsic dorsal horn neurons. Specifically, DAMGO, DPDPE, and deltorphin II reduced the amplitude of evoked EPSC/Ps in lamina II neurons at smaller concentrations than those required to blunt the postsynaptic response to AMPA (Glaum et al, 1994;Kohno et al, 1999). Similarly, DAMGO and the endogenous MOR-selective opioid peptides endomorphin I and II suppressed evoked glutamatergic EPSCs at smaller concentrations than those required to evoke significant outward hyperpolarizing inwardly rectifying K ϩ currents in lamina II neurons (Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, considerable evidence argues that MORand DOR-selective agents inhibit excitatory (glutamatergic) neurotransmitter release by C-fibers in a more potent manner than how they inhibit intrinsic dorsal horn neurons. Specifically, DAMGO, DPDPE, and deltorphin II reduced the amplitude of evoked EPSC/Ps in lamina II neurons at smaller concentrations than those required to blunt the postsynaptic response to AMPA (Glaum et al, 1994;Kohno et al, 1999). Similarly, DAMGO and the endogenous MOR-selective opioid peptides endomorphin I and II suppressed evoked glutamatergic EPSCs at smaller concentrations than those required to evoke significant outward hyperpolarizing inwardly rectifying K ϩ currents in lamina II neurons (Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 92%
“…Spinally administered δ-opioid agonists likely inhibit synaptic transmission through both pre-and postsynaptic mechanisms (Abbadie et al, 2002;Glaum et al, 1994;Kohno et al, 1999;Stewart and Hammond, 1993;Zachariou and Goldstein, 1996). The opioid receptors are coupled to inhibitory G proteins, and voltage-activated Ca 2+ channels are an important downstream signaling target for the opioid analgesic action.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the release of glutamate and substance P from primary afferent neurons is inhibited by δ-opioid agonists (Glaum et al, 1994;Kohno et al, 1999;Kondo et al, 2005). Thus, the presynaptic action of δ-opioid agonists on nociceptive afferent terminals has been considered an important mechanism underlying the spinal analgesic effect of δ-opioid agonists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, facilitated windup could result from an enhanced summation of excitatory synaptic inputs on secondary neurons by lifting the prominent presynaptic inhibition of neurotransmitter release. Because activation of postsynaptic MOR by endogenous opioids leads to membrane hyperpolarization (Yoshimura and North, 1983;Ruda et al, 1984;Glaum et al, 1994), enhanced windup in MOR Ϫ/Ϫ animals may result from the absence of MORs on the somatodendritic region of WDR neurons. However, it is unclear whether endogenous opioids released during 0.2 Hz stimulation are able to induce postsynaptic MOR signaling.…”
Section: Discussionmentioning
confidence: 99%